2022
DOI: 10.1038/s41380-022-01818-x
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol reverses the effects of KCNJ6 (GIRK2) noncoding variants on excitability of human glutamatergic neurons

Abstract: Synonymous and noncoding single nucleotide polymorphisms (SNPs) in the KCNJ6 gene, encoding G protein-gated inwardly rectifying potassium channel subunit 2 (GIRK2), have been linked with increased electroencephalographic frontal theta event-related oscillations (ERO) in subjects diagnosed with alcohol use disorder (AUD). To identify molecular and cellular mechanisms while retaining the appropriate genetic background, we generated induced excitatory glutamatergic neurons (iN) from iPSCs d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

5
0

Authors

Journals

citations
Cited by 9 publications
(39 citation statements)
references
References 69 publications
8
31
0
Order By: Relevance
“…In support of our finding that the upregulation of GIRK2 plays an important role in controlling neuronal excitability as well as modulating the response to ethanol, a recent study found that iPSC-derived human neurons derived from AUD-diagnosed participants containing specific KNJ6 SNPs had lower levels of GIRK2 expression, greater neurite area, and heightened excitability than neurons derived from unaffected individuals 6 . Overexpression of GIRK2 in neurons from AUD-diagnosed individuals mimicked the effects of the 7-day IEE protocol, eliminating differences in neuronal morphology induced excitability 6 . Thus, in the context of AUD, increased GIRK2 expression and subsequent neuronal inhibition appears to exert a normalizing influence.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…In support of our finding that the upregulation of GIRK2 plays an important role in controlling neuronal excitability as well as modulating the response to ethanol, a recent study found that iPSC-derived human neurons derived from AUD-diagnosed participants containing specific KNJ6 SNPs had lower levels of GIRK2 expression, greater neurite area, and heightened excitability than neurons derived from unaffected individuals 6 . Overexpression of GIRK2 in neurons from AUD-diagnosed individuals mimicked the effects of the 7-day IEE protocol, eliminating differences in neuronal morphology induced excitability 6 . Thus, in the context of AUD, increased GIRK2 expression and subsequent neuronal inhibition appears to exert a normalizing influence.…”
Section: Discussionsupporting
confidence: 84%
“…By contrast, 21-day IEE ↑GIRK2 neurons increased their latency to first spike with glutamate (+ 2.1 s, p = 0.0312 exposure effect; p < 0.00001 interaction effect) ( Figure 5C ). Similar to the measurements of spontaneous activity, ( Figure 4E-F ), calcium peak heights were significantly larger in IEE iso-CTL neurons (+ 0.36 ΔF/F 0 , p = 3×10 - 6 ), and this increase was not observed in ↑GIRK2 neurons ( Figure 5D ). Taken together, these data indicate that 21-day IEE heightens glutamate receptor activity and/or excitability in iso-CTL neurons, whereas ↑GIRK2 neurons exhibit diminished glutamate responses.…”
Section: -Day 17 MM Ethanol Protocol: Transcriptomic Evidence Of Down...supporting
confidence: 83%
See 3 more Smart Citations